Quantitative synthesis on the ecosystem services of cover crops - Daryanto, Stefani; Fu, Bojie; Wang, Lixin; Jacinthe, Pierre-André; Zhao, Wenwu (Earth-science reviews, 2018)
The maintenance of soil health in agro-ecosystems is essential for sustaining agricultural productivity. Through its positive impacts on various soil physical and biological processes, cover cropping can be an important component of sustainable agricultural production systems. However, the practice of cover cropping can be complex, and possible trade-offs between the benefits and side effects of cover crops have not been examined. To evaluate these benefits and potential trade-offs, we quantitatively synthesized different ecosystem services provided by cover crops (e.g., erosion control, water quality regulation, soil moisture retention, accumulation of soil organic matter and microbial biomass, greenhouse gas (GHG) emission, weed and pest control, as well as yield of the subsequent cash crop) using data from previous publications. We used a simple indicator (δ), defined as the ratio of an observed variable (i.e., ecosystem service) under cover crop and under fallow condition, to evaluate the impacts of cover crops on a given ecosystem service. Our results showed that cover crops provided beneficial ecosystem services in most cases, except for an increase in GHG emission (δCO2 = 1.46 ± 0.47 and δN2 O = 1.49 ± 1.22; x¯ ± SD) and in pest (nematode) incidence (δnematode abundance = 1.29 ± 1.61). It is also important to highlight that, in some cases, tillage could offset the extent of ecosystem service benefits provided by cover crops. Based on this synthesis, we argue that cover crops should be incorporated into modern agricultural practices because of the many environmental benefits they offer, particularly the maintenance of soil and ecosystem health. More importantly, there was generally an increase in cash crop yield with cover cropping (δyield = 1.15 ± 0.75), likely due to improvement in various soil processes. Despite its benefits, the complexity of cover crop management should not be overlooked, and site-specific factors such as climate, soil type, cover crop species and tillage practices must be considered in order to optimize the benefits of cover cropping. In addition to crop yield, detailed economic analyses are needed to calculate the direct (e.g., reduction in the amount of chemical fertilizer) and indirect monetary benefits (e.g., the improvement of soil quality) of cover crops. Such a comprehensive analysis could serve as incentive for producers to integrate cover crops into their management practices.